2020
DOI: 10.21203/rs.3.rs-97021/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico Investigation of Saponins and Tannins as Potential Inhibitors of SARS-CoV-2 main Protease (Mpro)

Abstract: It is no longer news that a novel strain of coronavirus named SARS-CoV-2 is ravaging the health sector worldwide, several attempts have been made to curtail this pandemic via repurposing of old drugs but at the present, available drugs are not adequately effective. Over the year, plant phytochemicals are increasingly becoming an alternative source of an antimicrobial agent with a novel mechanism of action and limited side effects compared to synthetic drugs. Isolated saponins and tannins were evaluated for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Cytochrome P450 inhibitors are responsible for the biotransformation of a drug; a potential drug should not alter their kinetics [34]. Te results show that although compounds 1 (2/5), 2 (3/5), 3 (4/5), and 5 (3/5) violated the minimum inhibition allowed as reported by Falade et al [19], compounds 8 (0/5), 9 (0/5), 12 (1/5), and 13 (0/5) show an improved value of less inhibition compared to chloroquine (2/5).…”
Section: Admet Studiesmentioning
confidence: 56%
See 2 more Smart Citations
“…Cytochrome P450 inhibitors are responsible for the biotransformation of a drug; a potential drug should not alter their kinetics [34]. Te results show that although compounds 1 (2/5), 2 (3/5), 3 (4/5), and 5 (3/5) violated the minimum inhibition allowed as reported by Falade et al [19], compounds 8 (0/5), 9 (0/5), 12 (1/5), and 13 (0/5) show an improved value of less inhibition compared to chloroquine (2/5).…”
Section: Admet Studiesmentioning
confidence: 56%
“…Te receptor was obtained from the (RCSB) database (https://www.rcsb.org/pdb). Te resolution of receptor 5TBO (2.15 Å) approximately lies about the 2.0 Å recommended resolution for a receptor of good quality [19]. Water molecules around the crystal structure and other associated inhibitors were removed from the downloaded protease to avoid undesired interferences and unwanted molecular interactions.…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponins including triterpenoid saponins derived from various medicinal plants have also been investigated for their therapeutic potential against SARS-CoV-2 (Ebob, Babiaka & Ntie-Kang, 2021). But, most are based on in silico studies (Diniz, Perez-Castillo, Elshabrawy, Filho & de Sousa, 2021;Falade, Adelusi, Adedotun, Abdul-Hammed, Lawal & Agboluaje, 2021;Sinha et al, 2021;Yang et al, 2020) and it is only recently that their inhibitory activities have been demonstrated using pseudotyped or authentic SARS-CoV-2. Licoricesaponin A3, a triterpenoid saponin isolated from licorice, was reported to inhibit SARS-CoV-2 by targeting the NSP7, a core component of RdRp (Yi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There has been no report on the simultaneous synergistic effect of Chrysopogon zizanioides against M pro 30 . The top-ranked Apart from essential oils, the antiviral potentials of various flavonoid polyphenols, alkaloids, saponins, tannins, terpenoids, etc., were studied [35][36][37][38][39] . No compounds possessed toxicity and carcinogenic properties predicted using SwissADME and admetSAR webservers (Table 4), thus are safe for consumption without any side effects.…”
Section: Validation Of Docking Proceduresmentioning
confidence: 99%